2013
DOI: 10.3390/lubricants1020048
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Lubricants Containing Phosphate Ester Additives and Stainless Steels

Abstract: One way to improve fuel efficiency in today’s jet aircraft engines is to create an environment for higher operating temperatures and speeds. New and improved lubricants and bearing materials must be developed to remain stable in these elevated operating temperatures. Three lubricants, with varying amounts of tricresyl phosphate added as an anti-wear/extreme pressure additive were tested on two different stainless steels at varying temperatures ranging from 300 °C to 350 °C in vacuum. Significant decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Anionic phosphate ester additives are generally used as corrosion inhibitors, rust inhibitors, friction modifiers and extreme pressure (EP) anti-wear additives [29][30][31][32][33][34][35][36][37][38][39][40][41]. Their molecular structure mainly contains a phosphate head and a hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic phosphate ester additives are generally used as corrosion inhibitors, rust inhibitors, friction modifiers and extreme pressure (EP) anti-wear additives [29][30][31][32][33][34][35][36][37][38][39][40][41]. Their molecular structure mainly contains a phosphate head and a hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-wear additives have vital importance under extreme pressure (EP) conditions where the oil film between contacting surfaces is not sufficiently thick to prevent direct contact between the surface asperities. In such conditions, ideal additives form robust anti-wear films that adhere strongly to the surfaces and also withstand higher temperatures, particularly in aviation engines that operate at higher temperatures and higher speeds [4,5]. Phosphate esters and (metal) thiophosphate esters have been used as lubricant additives for more than 50 years in both the automotive and aviation industries.…”
Section: Introductionmentioning
confidence: 99%
“…The WSD of the oil containing TiO 2 under the NP or the TP increased when the concentration was beyond the optimum concentration. This can be interpreted as granule abrasions that take place in the presence of excess nanoparticles in the friction area [25,33,39]. However, it is observed that the anti-wear property of the TiO 2 nanoparticles both under the TP and under the NP is better than that of the base oil (see Figure 3).…”
Section: Anti-wear and Friction-reducing Properties Of Tio2 Nanopartimentioning
confidence: 99%
“…Inter alia, titanium dioxide (TiO 2 ) nanoparticles as lubricant additive were studied with much more attention, because of their good performance on anti-oxidant features, relatively low toxicity, pleasant odor, and non-volatility [25][26][27]. Unfortunately, nanoparticles are not well dispersed in nonpolar organic solvents due to their oleo-philic property, which limits the nanoparticles applications in lubricants.…”
Section: Introductionmentioning
confidence: 99%